Does Organizational Cronyism Lead to Lower Employee Performance? Examining the Mediating Role of Employee Engagement and Moderating Role of Islamic Work Ethics - Shaheen, Sadia; Zulfiqar, Sehar; Saleem, Sharjeel; Shehazadi, Gulshan (Frontiers in Psychology, 2020)
In this research, using a time-lagged approach, we investigated the relationship between organizational cronyism and employee performance. Drawing on the conservation of resources theory, we tested the mediating role of employee engagement in the relationship between organizational cronyism and employee performance. We also examined how Islamic work ethics moderated the relationship between organizational cronyism and work engagement. The study, with a total of 267 participants, was conducted in the healthcare sector of Pakistan. The results revealed that organizational cronyism was negatively related to employee performance. The analyses confirmed the mediating role of work engagement in the relationship between organizational cronyism and employee performance. Similarly, Islamic work ethics moderated the relationship between organizational cronyism and work engagement. Implications for future research as well as managerial implications of our findings along with the limitations and future research directions are also discussed.